Cross-disciplinary craftsmanship: The case of child abuse work. (September 2017) - Davidov, Jonathan; Sigad, Laura I; Lev-Wiesel, Rachel; Eisikovits, Zvi
Child abuse is a complex social problem that cannot be understood from a single disciplinary perspective. Successful intervention requires involvement of various professional groups. While such cooperation has many potential advantages, in practice, it presents challenges to effective intervention. The present study examines the lived experience of professionals in Israel engaging in cross-disciplinary intervention in child abuse. Qualitative data were collected by means of 40 in-depth interviews with professionals, including law enforcement agents, educators, mental health, and medical personnel. Two interrelated dynamics emerged: (a) responsiveness, based on immediacy, and (b) attempts to account for the intervention performed from the specific professional viewpoint of the intervening person and his/her professional belonging. A conceptual model is suggested that reframes child abuse work as an ever-emerging creative process, involving professionals' attempts to balance the two dynamics in their daily work. Their cross-disciplinary activities are improvisational and situational, involving trial and error. Implications for practice are suggested.